Systemic sustainability reporting in educational institutions : a comparative investigation into sustainability reporting on secondary science school websites in England - Dowsett, Anthony Noel Percival (Curtin University, 2013)
There is increasing discussion on the issues of resource use and sustainability in society in general and in education in particular. The United Nations (UN) organisation and the United Kingdom (UK) government, similar to other Western Nations around the world (Australasian, European, North American), are engaging with sustainable development issues and the need for education to addressing the challenge this presents.Increasingly, education institutions, corporations and non-governmental bodies are taking on the agenda of sustainability reporting. This is to meet legislative requirements, provide leadership, demonstrate commitment to transparency and address concerns for stakeholder accountability.The issue of accountability and transparency in the operation of many educational institutions is under greater scrutiny and consideration. A major area for investigation and research is the increased use by institutions of the medium of the internet to function as an outlet for information reporting to stakeholders and interested parties.This thesis investigates secondary school websites in England to review their sustainability activities in a systemic way and assess their level in terms of sustainability initiatives, including transparency and accountability to their constituent stakeholders. The research for this thesis focuses on the evaluation of sustainability reporting in UK secondary schools. There are a range of curricula areas that naturally connect with this agenda. Science specialist schools are of interest as the positivist Western science creates a driver to awareness, capacity for empiricism and ability to understand complex issues, which can inform debate and decisions on development for a sustainable future.Through the disclosure framework of stakeholder theory, a content analysis of the publicly available information on school websites identifies to what extent there is evidence of an educational institution's sustainability through selected keywords. This is undertaken within a pragmatic framework to analyse the reporting regimes of secondary schools with specialist science status. The study elucidates to what extent sustainability issues are systemically incorporated, discussed and disclosed publically in the secondary education sector utilising the medium of the web-based internet.A range of exemplary schools are provided as comparative examples for discussion of the effectiveness of the science specialist schools. This is within the context of the recent and ongoing changes in the state school sector in the UK. The sample of specialist science schools in England, were assessed for positive association with the keyword parameters to analyse improved performance when compared to a control group and the secondary education population as a whole in England. The conclusion, based on results from the analysis of the data, and the literature, indicates that there is an increased opportunity to make improvements to the current reporting of sustainability initiatives and school activities.Selected changes to the internet-based web facility to improve engagement with stakeholders would include sustainability of schools in a more systemic way with the financial, operational, educational and performance achievements which are currently disclosed. Information presented on the web increases valued connections to provide transparency, accountability and improved availability that may have other beneficial effects for the school stakeholders, the local community and beyond. Further research would also benefit policy makers and stakeholders through an integrated sustainability reporting format that encompasses educational activities, outcomes and operations of a school, providing the basis for systematically using a web interface to provide improved disclosure and accountability.